PENGGUNAAN CULTIVATOR POWER WEEDER SEBAGAI PENGENDALI GULMA SECARA MEKANIS PADA TANAMAN SAYURAN - Hasanuddin, Hasanuddin; ., Jauharlina; Agustina, Raida; Munawar, Agus Arip (Universitas Syiah Kuala, 2024)
Farmers in Lieue Village, Darussalam District, Aceh Besar still use the handweeding method to control weeds in vegetable crops. This method takes a long time, making the weed control process less effective. In addition, the small amount of labor is not proportional to the area of vegetable crops, so the weed control method is less efficient. To overcome this, the partner community is offered a solution to the mechanical weed control method, namely by using a cultivator power weeder. The weed control tool offered is an engine-driven tool mounted on an iron frame with two iron wheels equipped with blades that function as soil cultivators and weed cutters. When the machine is turned on and running, the soil will be processed while cutting weeds and controlling weeds. The cultivatorpower weeder offered is an innovation developed by the Weed Management Laboratory of the Agrotechnology Study Program and the Agricultural Equipment and Machinery Laboratory of the Faculty of Agriculture, Syiah Kuala University. It is hoped that with this weed control tool, the weed control process in vegetable crops can be more effective and efficient and ultimately can increase the yield of vegetable crops of farmers in Aceh Besar.The results of the service showed that the service team had succeeded in making a power weeder cultivator as a mechanical weed controller using a driving machine. However, the tool that has been made turns out to be rather difficult to move. Therefore, wheels were added to the front to make it easier to move. This tool can be used for weed control in horticultural and food crops. To date, farmers have tried and used the power weeder cultivator as a mechanical weed controller to control weeds in vegetable crops in various target villages.